DINAMIKA PERAN ELITE LOKAL PASCA ORDE BARU : Studi Kasus di Sumbawa - Satriani, Septi (Jurnal Penelitian Politik, 2011)
This study is to describe the role of local aristocracy and various factors that bring about inability of thearistocracy to redefine their roles and existencee while in area ofIndonesia local aristorats are able to do soThis study also examines impact ofchanges and continuity ofthe role ofthe aristocracy towards local democracyin Sumbawa